PELAKSANAAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN PJOK PADA MASA PANDEMI COVID-19 DI SMKN 1 SUKABUMI - Dinda Istiqomah, - (2022)
The purpose of this study is to describe the implementation of character education in social studies at sm1 using a corelational approach. The study's population xi student class of the 95 electrical installation engineering program and 3 master. By the size of 74 samples determined to the extent of significant 5% recommended by sugiyono, each sample next is determined by a propotional random sampling technique. Data is collected with questionnaires and interviews with qualitative and quantitative descriptive data analysis. The results of this study show that successful implementation of character education in either category is sufficient or can be said to be successful with the following implementation of education of character: (1) the appropriate character education of honesty, discipline, manners/ethics, responsibility, cooperation, confidence and creativity. (2) the performance of character learning is done through long-distance learning through a video or picture with a character education in it. (3) the value of achieving the quality of the implementation of the program for the cultivation of virtue of students is based on the aspect of honesty, discipline, manners, responsibility, cooperation, confidence, and creativity of 74 student respondents in the category enough to meet the quality attainment score of 23 or (31%). Key words: Learning, Physical Education, Character Assessment